Framing the Forgotten: Beauty, Innocence, and Religiosity in the Representation of Indonesian Comfort Women - Az-Zahra, Nur Aisyiah (East Asian Review, 2025)
This research examines the documentary *Because We Were Beautiful* (2010), which focuses on the testimonies of Indonesian *juugun ianfu* (military comfort women) who experienced sexual violence during the Japanese occupation of the Netherlands East Indies (present-day Indonesia) from 1942 to 1945. Framed through a feminist lens, this study utilizes Cockburn's concept of "war as a continuum" to explore how the documentary portrays the "post-war" lived realities of *ianfu*. The main research questions are: (1) What dominant themes emerge in *Because We Were Beautiful* (2010) that frame the testimonies of the former *ianfu*? (2) How does the documentary represent how these former *ianfu* remember and forget their "post-war" experiences? This study employs documentary film analysis with a constructionist approach to examine how *Because We Were Beautiful* represents the narratives of former Indonesian *ianfu*. This article argues that the documentary serves as a redemptive effort by the Western colonizer (the Netherlands) toward its colonized subjects (Indonesia), while simultaneously vilifying its Eastern colonizer counterpart (Japan). Furthermore, the documentary reflects the Dutch perspective on Indonesian comfort women "under Western eyes"—borrowing from Mohanty's term—by reproducing Western stereotypes of colonized Third World women as physically beautiful, sexually innocent, and religiously devout. This research highlights how postcolonial narratives of gender, memory, and violence intersect in the screen representation of wartime trauma.